Comparison between clinical gait and daily‐life gait assessments of fall risk in older people - Brodie, Matthew A.; Coppens, Milou J.; Ejupi, Andreas; Gschwind, Yves J.; Annegarn, Janneke; Schoene, Daniel; Wieching, Rainer; Lord, Stephen R.; Delbaere, Kim (Geriatrics & gerontology international, 2017)
Aim Falls are a leading cause of disability in older people. Here we investigate if daily‐life gait assessments are better than clinical gait assessments at discriminating between older people with and without a history of falls. Methods A total of 96 independent‐living participants (age 75.5 ± 7.8) underwent sensorimotor, psychological and cognitive assessments, and the Timed Up and Go and 10‐m walk tests. Participants wore a small pendant sensor device for a week in their home environment, from which the new remote assessments of daily‐life gait were determined. Results During daily‐life, fallers had significantly lower gait quality (lower gait endurance, higher within‐walk variability and lower between‐walk adaptability), but not reduced gait quantity (total steps) or gait intensity (mean cadence). In the clinic, fallers had slower Timed Up and Go, but not 10‐m walk test times. After adjusting for demographics, only the daily‐life assessments of gait endurance and within‐walk variability remained significant. Reduced daily‐life gait assessments were significantly correlated with older age, higher body mass index, multiple medications, disability, more concern about falling, poor executive function and higher physiological fall risk. Conclusions The new daily‐life gait assessments were better than the clinical gait assessments at identifying fall risk in our sample of independent living older people. However, further research is required to validate these findings in other populations or those living in residential aged care. Daily‐life gait was not only associated with demographics and physiological capacity, but also general health, executive function and the ability to undertake a variety of activities of daily living without excessive concern about falling. Geriatr Gerontol Int 2017; 17: 2274–2282.